008: QUALITY OF LIFE AMONG INSTITUTIONALIZED AND COMMUNITY-DWELLING FILIPINO ELDERLY. (24th August 2015) - Flormata, Mischelle Diwa; Vargas, Marie Ann Sunga
Abstract : Background: The present situation of our country is almost similar to other developing countries. The aging population continuously increased at a fast phase. Objectives: Thus, the study aims to identify the quality of life of the Filipino elderly population, amongst those who are living in the community compared to those who are living in private or government-run institutions. A sample of 406 Filipino elderly (124 men and 282 women) aged 60 to 90 years voluntarily participated in the study. Methods: The study utilized mixed method research of descriptive and phenomenological research designs using QoL-OLD questionnaire obtained from the World Health Organization and QoL Assessment Resident Interview. The sampling technique is purposive sampling for the quantitative part and simple random sampling for the qualitative part for the respondents who answered the questionnaires on both groups of samples. Demographic profiles (such as age, gender, marital status, educational attainment, and previous jobs) of the subjects were taken to be reviewed and analyzed as factors in their perception of quality of life. Result: The results of the administered QoL-OLD questionnaire were tallied and evaluated according to the corresponding scores and interpretation based on the standard protocol set in the manual. The statistical treatment employed was t-Test. The phenomenological part of the study with 32 respondents, conversely aimed to capture the individual and collective experiences and perspectives of both group of samples who come from different living arrangement (in the community and in the institution). Face to face in-depth interview were tape recorded (with the permission of the interviewee) and transcribed. Data transcriptions were then coded, categorized and analyzed into individual and common themes for data triangulation alongside the quantitative part. Conclusion: The result of the study contributes significantly to the current scientific literature regarding the Quality of Life through the perspective of the elderly in the country. Thus, the researcher recommends the inclusion of the outcome of the study on the existing programs that we have for the elderly so that it is geared towards the improvement of their quality of life.